Computer Equity: Implications for Educational Policy and School Leadership - Richard King (Educational Considerations, 1986)
Computer equity is broader than mere access. . . Computer inequity is the unequal access to computer learning as consequences of a student's social and economic position . . . or willingness of schools to provide computer experiences.